Adar is essential for optimal presynaptic function. - Maldonado, C.; Alicea, D.; Gonzalez, M.; Bykhovskaia, M.; Marie, B. (Molecular and Cellular Neurosciences, 2013)
RNA editing is a powerful way to recode genetic information. Because it potentially affects RNA targets that are predominantly present in neurons, it is widely hypothesized to affect neuronal structure and physiology. Across phyla, loss of the enzyme responsible for RNA editing, Adar, leads to behavioral changes, impaired locomotion, neurodegeneration and death. However, the consequences of a loss of Adar activity on neuronal structure and function have not been studied in detail. In particular, the role of RNA editing on synaptic development and physiology has not been investigated. Here we test the physiological and morphological consequences of the lack of Adar activity on the Drosophila neuromuscular junction (NMJ). Our detailed examination of synaptic transmission showed that loss of Adar increases quantal size, reduces the number of quanta of neurotransmitter released and perturbs the calcium dependence of synaptic release. In addition, we find that staining for several synaptic vesicle proteins is abnormally intense at Adar deficient synapses. Consistent with this finding, Adar mutants showed a major alteration in synaptic ultrastructure. Finally, we present evidence of compensatory changes in muscle membrane properties in response to the changes in presynaptic activity within the Adar mutant NMJs.